Inside Cover: Selective Luminescent Labeling of DNA and RNA Quadruplexes by π‐Extended Ruthenium Light‐Up Probes (Chem. Eur. J. 21/2017). Issue 21 (14th February 2017) - Saadallah, Dounia; Bellakhal, Mehdi; Amor, Souheila; Lefebvre, Jean‐François; Chavarot‐Kerlidou, Murielle; Baussanne, Isabelle; Moucheron, Cécile; Demeunynck, Martine; Monchaud, David
Abstract : Ru II complexes with π‐extended, acridine‐based ancillary ligands display high affinity and selectivity for DNA and RNA quadruplexes along with remarkable light‐up properties that enable them to discriminate quadruplexes from genomic DNA. The in vitro and in cellulo results of the most promising candidates {i.e., [Ru(phen)2 (Cl‐dpqp)]Cl2 and [Ru(bpy)2 (Br‐dpqp)]Cl2 } shown here confirm the interest of this new family of luminophores as invaluable molecular tools to track and visualize G‐quadruplexes in cells. More information can be found in the Communication by C. Moucheron, M.  Demeunynck, D. Monchaud, et al. onpage 4967 ff.